Penerapan Kebersihan terhadap Penyebaran Lalat di Kantin Kampus 1 Iakn Tarutung - Siti Aisyah; Angelia Putriana; Apriliani Lase; Sabam Syahputra (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
This study aims to analyze the impact of cleanliness on the spread of flies in the cafeteria of Campus 1 IAKN Tarutung. Cleanliness is a crucial factor in managing the cafeteria, as unhygienic conditions can lead to an increase in fly populations, which have the potential to transmit various diseases through food contamination. This research employs a qualitative method with direct observation of the cafeteria's cleanliness and interviews with cafeteria managers and visitors. The results indicate that inadequate cleanliness, such as poorly managed waste and the accumulation of food scraps, is a primary factor attracting flies to the cafeteria area. Additionally, the lack of awareness among cafeteria managers regarding the importance of maintaining cleanliness exacerbates this issue. Based on these findings, it is recommended that the campus authorities improve cleanliness standards by providing cleanliness education to cafeteria managers and visitors, as well as implementing a more effective waste management system. By doing so, it is expected to reduce the fly population and enhance the safety and comfort of the food served in the cafeteria.